Contextual design choices and partnerships for scaling early child development programmes. (12th April 2019) - Milner, Kate M; Bernal Salazar, Raquel; Bhopal, Sunil; Brentani, Alexandra; Britto, Pia Rebello; Dua, Tarun; Gladstone, Melissa; Goh, Esther; Hamadani, Jena; Hughes, Rob; Kirkwood, Betty; Kohli-Lynch, Maya; et al.
Abstract : Translating the Nurturing Care Framework and unprecedented global policy support for early child development (ECD) into action requires evidence-informed guidance about how to implement ECD programmes at national and regional scale. We completed a literature review and participatory mixed-method evaluation of projects in Saving Brains®, Grand Challenges Canada® funded ECD portfolio across 23 low- and middle-income countries (LMIC). Using an adapted programme cycle, findings from evaluation related to partnerships and leadership, situational analyses, and design for scaling ECD were considered. 39 projects (5 'Transition to Scale' and 34 'Seed') were evaluated. 63% were delivered through health and 84% focused on Responsive Caregiving and Early Learning (RCEL). Multilevel partnerships, leadership and targeted situational analysis were crucial to design and adaptation. A theory of change approach to consider pathways to impact was useful for design, but practical situational analysis tools and local data to guide these processes were lacking. Several RCEL programmes, implemented within government services, had positive impacts on ECD outcomes and created more enabling caregiving environments. Engagement of informal and private sectors provided an alternative approach for reaching children where government services were sparse. Cost-effectiveness was infrequently measured. At small-scale RCEL interventions can be successfully adapted and implemented across diverse settings through processes which are responsive to situational analysis within a partnership model. Accelerating progress will require longitudinal evaluation of ECD interventions at much larger scale, including programmes targeting children with disabilities and humanitarian settings with further exploration of cost-effectiveness, critical content and human resources.